On the equivalence of matrices over commutative rings modulo ideals - Bondarenko, V.M.; Tylyshchak, A.A.; Stoika, M.V. (Algebra and Discrete Mathematics, 2014)
We study connections between wildness of the problem of classifying the matrices over an integral domain up to equivalence modulo an ideal and properties of the set of prime elements of the domain.